PENERAPAN TEMA ARSITEKTUR INDUSTRIAL PADA THE TIING HOTEL, TEJAKULA, BULELENG - Yoni, Ida Ayu Putu padmi; Saidi, Agus Wiryadhi; Witari, Made Ratna (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2022)
The Tiing Hotel is a four-star accommodation facility located in Tejakula District, Buleleng Regency, Bali Province. This architectural work is interesting to discuss because it comes with a unique industrial architecture theme. The industrial architectural style appears with the characteristic of using basic materials as they are without significant processing which gives the impression of being unfinished, firm, masculine and honest. The industrial architecture theme at The Tiing Hotel is unique because of the mix of cement/concrete with bamboo which is widely used in its design. Generally, the dominant industrial architecture uses modern materials produced by factories or former factory buildings. This study examines and analyzes how the architects of The Tiing Hotel designed and implemented industrial architectural themes in their designs. This research is qualitative in nature. Data sourced from secondary data were analyzed using descriptive methods. The conclusions obtained show that The Tiing Hotel applies the theme of industrial architecture with a modern minimalist nuance in a rural Balinese natural setting. The character of industrial architecture can be seen in the shape of the building and the firm lines; unfinished floor, wall, ceiling surfaces; the original color of the material and exposed surface. No visible exposure to mechanical-electrical elements. The combination with natural elements can be seen from the arrangement of the building site in response to its environment; exposed concrete wall materials with bamboos and natural stones; furniture and decoration with natural materials.